2022
DOI: 10.1186/s13052-022-01395-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of selected interleukins (IL-6, IL-17A, IL-18, IL-23) and chemokines (RANTES, IP-10) in children with acute and chronic urticaria

Abstract: Background Urticarial lesions develop as a result of the activation of mast cells which, through the release of mediators, influence the formation of local inflammatory infiltrates. Changes in the expression of many cytokines and chemokines are observed in the course of urticaria. The aim of the study was to evaluate serum levels of interleukin (IL)-6, IL-17A, IL-18, IL-23, regulated on activation, normal T cell expressed and secreted (RANTES) and interferon (IFN)-γ-inducible pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The obtained results generally agreed with Góra et al [15]mentioned the parameters (WBC,EO,IgE,IL-6 ) higher in patient with acute and chronic urticarial than control group , as well as agreed with Jang et al [16] the serum IgE higher in the patients IgE modulates mast cell activation and releases histamine, lipid mediators, kinins, and cytokines, which contributes to the development and severity of CSU by interacting with a high-affinity IgE receptor (FcRI) found on cutaneous mast cells and basophils [17].…”
Section: Biomarkers Between Csu Patients and Control Subjectsupporting
confidence: 91%
See 1 more Smart Citation
“…The obtained results generally agreed with Góra et al [15]mentioned the parameters (WBC,EO,IgE,IL-6 ) higher in patient with acute and chronic urticarial than control group , as well as agreed with Jang et al [16] the serum IgE higher in the patients IgE modulates mast cell activation and releases histamine, lipid mediators, kinins, and cytokines, which contributes to the development and severity of CSU by interacting with a high-affinity IgE receptor (FcRI) found on cutaneous mast cells and basophils [17].…”
Section: Biomarkers Between Csu Patients and Control Subjectsupporting
confidence: 91%
“…The findings were agreed to [15], the largest area under the curve (AUC) was found for IP-10 (AUC= 0.98; p 0.001), for which the optimal cut-off value determined by the Youden index was 55.10. The sensitivity and specificity of IP-10 as a biomarker of urticaria incidence were determined to be 92% and 100%, respectively.…”
Section: Sensitivity Roc Curvesupporting
confidence: 73%
“…Thus, duration of pruritus may not be the most reliable indicator of disease progression and prognosis. Moreover, Velasco-Ortega et al (2022) (17) found a correlation between multiple in ammatory factors and CSU, and these factors are associated with different immune cells and in ammatory mediators. Therefore, the interaction of various in ammatory factors may affect the severity and development of CSU.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, duration of pruritus may not be the most reliable indicator of disease progression and prognosis. Moreover, Góra et al [17] found a correlation between multiple inflammatory factors and CSU, and these factors are associated with different immune cells and inflammatory mediators. Therefore, the interaction of various inflammatory factors may affect the severity and development of CSU.…”
Section: Discussionmentioning
confidence: 99%